Research Methods for Business Students. - Saunders, Mark.; Lewis, Philip; Thornhill, Adrian; ProQuest (firma) (Harlow : Pearson Education, Limited, 2023)
Support your students' research project with robust and pragmatic guidance on the entire process. Research Methods for Business Students introduces a range of features, including a glossary of terms, case studies and articles, and self-study prompts that will encourage your students to apply what they have learned to their own research project.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books